From trauma to resilience: psychological and epigenetic adaptations in the third generation of holocaust survivors - Guy Oren; Anat Shoshani; Nadra Nasser Samra; Willem JMI Verbeke; Pascal Vrticka; Daniela Aisnberg-Shafran; Tsachi Ein-Dor (Scientific Reports)
Abstract The transmission of trauma across generations, particularly among descendants of Holocaust survivors, presents a complex interplay of psychological and epigenetic adaptations. This study explored the long-term impacts of Holocaust trauma on the third and fourth generations, focusing on the quality of social-emotional ties and psychopathology, as well as the epigenetic variation in the oxytocin system, the Hypothalamic-Pituitary-Adrenal (HPA) stress axis, and the Sympathetic Nervous System (SNA). Involving 371 participants, including 186 third- and fourth-generation descendants of Holocaust survivors (54.8% women, mean age = 29.67), we employed DNA methylation analysis of saliva samples to uncover these dynamics. Our findings revealed that descendants exhibited significantly lower general attachment avoidance, and a DNA methylation pattern associated with stronger activation of the oxytocin system, indicating enhanced social bonding and social emotion regulation. Conversely, they showed distinct DNA methylation patterns in CRH, CRHBP, FKBP5, and NR3C1 genes linked to increased HPA axis activation and more pronounced stress reactivity. Despite the presence of these two DNA methylation patterns, no elevated levels of psychopathology were observed. Our results highlight the dual nature of trauma transmission, with descendants displaying both vulnerabilities and resilience. While stronger oxytocin system activation may support social cohesion and stress reduction, stronger HPA axis reactivity could ensure sustained vigilance and preparedness. Our findings thus underscore the intricate balance between genetic, epigenetic, and environmental factors in shaping resilience and offer insights into the potential for long-term growth following inherited trauma.